Mass Effect of Coconut Shell-derived Activated Carbon on Adsorption of Benzene, Toluene, Ethylbenzene, and Xylene in Motorcycle Emissions - Trisna Yuliana; Aini Aspiati Rohmah; Yusuf Eka Maulana; Arie Hardian (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2021)
The use of motorized transportation in Indonesia is now proliferating. The higher the use of motorized vehicle-based transportation in an area, the higher the potential for air pollution. One of the air pollutants is a mixture of benzene, toluene, ethylbenzene, and xylene (BTEX). This study examines the effect of coconut shell-derived activated carbon adsorbent mass which is adjusted with different thicknesses on its adsorption ability for BTEX. The adsorbent is used to adsorb the emissions of the 1990 GL-Pro motorcycle with premium fuel. The results of gas chromatography-mass spectroscopy (GC-MS) show that motor vehicle emissions contain BTEX and other hydrocarbons. ANOVA variant analysis showed that the difference in mass of activated carbon in the range of this study did not provide a significant difference in BTEX adsorption.Keywords: adsorbent; motor vehicle emissions; BTEX pollutants; coconut shell